Teacher's Perception, knowledge, attitude, and practice and their assessment of eco-friendly program implementation in Eastern Visayas, Philippines a correlational study - Lagunzad, Maria Glenda C.; Casas, Eulito V. (2024)
This study investigated the correlation between teachers' perceptions and the assessment of Information, Education, and Communication (IEC) materials in implementing eco-friendly programs in selected schools in the Eastern Visayas Region. A quantitative research design was employed, utilizing a Google Forms survey questionnaire to measure teachers' perceptions, knowledge, attitudes, practices, and evaluations of IEC materials. The sample comprised 152 teachers from various schools within the region, purposefully selected as respondents. Statistical analyses, including frequency, percentage, mean, Pearson's correlation coefficient, cross-tabulation, and Chi-square tests, were employed to analyze the data. The findings showed high levels of environmental knowledge, positive perceptions, and attitudes toward eco-friendly practices among teachers. However, certain areas revealed misconceptions, highlighting the need for ongoing education and training initiatives. Evaluation of IEC activities indicated high relevance and accuracy, though opportunities for enhancement were identified. A significant correlation emerged between teachers' perception and their assessment of IEC materials, suggesting potential avenues for improving environmental education programs. These findings emphasize the importance of ongoing professional development and refinement of educational resources to support environmentally sustainable practices in schools.
Master's thesis (Master of Science in Environmental Science) -- University of the Philippines, Tacloban.